Implementasi Virtual Reality Desain Arsitektur Perumahan 3D Sebagai Media Promosi Bisnis Investasi Properti Berbasis Android - Faisyal Rochimul Amri; Cindy Taurusta (Forum Kerjasama Pendidikan Tinggi, 2021)
The consumer is the target of all companies to offer the goods and services they have. Various kinds of promotions are carried out in order to attract the interest of consumers so the company can get maximum sales figures. Until now there are still many companies that do not maximize technology for media promotion, especially in the media promotion of residential architecture design. The research entitled